Développement du secteur financier et financement de l’activité agricole dans un contexte de crise alimentaire : quelle place pour la micro-finance ? - Sandra Kendo (Développement Durable et Territoires)
In a context of growing food crisis and where more than one billion people endure hunger, the study of the optimization of the agriculture sector, through the strengthening of the financing means in other to help a big number of poor reveals all its importance. The paper examines how microfinance can favorably contribute to improve the agriculture financing in other to encourage an improvement of life conditions of the poor populations. Innovation and adaptation to the needs of farmers can be instrumented by microfinance. Capacity of farm households has a double influence on the process of poverty reduction : i) through the productivity of agricultural households on the one hand, ii) and the distribution of income on the other hand. This article evaluates both the impact that the financial sector can have on the agricultural productivity and the potential impact of the latter on poverty. Indeed, if the financial sector in general doesn't contribute to improve agricultural productivity it is, however, an important instrument that positively acts in the process of poverty reduction. Besides, there is a negative and non linear relationship existing between agricultural productivity and poverty. The action of the financial sector to the agriculturists can be improved through microfinance, which should then be enhanced and popularized. The development of an adequate and adapted financing through the microfinance in the agricultural sector should be a priority for West African Countries. This will allow a positive influence both on the agricultural productivity process and on poverty reduction process.